On a Differential Equation Involving Hilfer-Hadamard Fractional Derivative - M. D. Qassim; K. M. Furati; N.-E. Tatar (Abstract and Applied Analysis)
This paper studies a fractional differential inequality involving a new fractional derivative (Hilfer-Hadamard type) with a polynomial source term. We obtain an exponent for which there does not exist any global solution for the problem. We also provide an example to show the existence of solutions in a wider space for some exponents.